Implementation of Religious Learning at Kindergarten Kemala Bhayangkari 01 Banjarmasin - Rizki Noor; Riska Safitri (Universitas muhammadiyah Banjarmasin, 2024)
Indonesia is an archipelagic country that has cultural, ethnic and religious diversity, so schools implement religious learning. The aim of this research is to describe planning, implementation, evaluation, as well as supporting and inhibiting factors for the implementation of religious learning. The research method used is a qualitative approach with a case study type of research. The subjects of this research were class B teachers, Islamic religious teachers, Christian religious teachers, and group B children. The data collection techniques used were observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of research on planning showed that all children were facilitated without discrimination, in 2017 there was Islamic and Christian religious learning but it was not included in the RPPH because the routine activity schedule was once a week, while theme learning was included in the RPPH which had been made by Kindergarten teacher Kemala Bhayangkari 01 Banjarmasin. In the implementation of religious learning once a week on Fridays, while learning is on a theme each semester. In the learning evaluation themes are in the form of anecdotal notes and checklists. Meanwhile, religious learning is a checklist. Supporting factors are the presence of Christian religious learning teachers, the enthusiasm of the teachers, and communication between teachers and parents. Meanwhile, the inhibiting factors are the child's lack of understanding, lack of time, and the child feeling afraid and sad from being in a different room and teacher.